Stationary distributions and mean first passage times of perturbed Markov chains - Hunter, Jeffrey J. (Massey University, 2002)
Stationary distributions of perturbed finite irreducible discrete time Markov chains are intimately connected with the behaviour of associated mean first passage times. This interconnection is explored through the use of generalized matrix inverses. Some interesting qualitative results regarding the nature of the relative and absolute changes to the stationary probabilities are obtained together with some improved bounds.
Keywords: Stationary distribution; Markov chains; First passage time